Photocatalytic Decolorization of Crystal Violate Dye Solution by ZnO/MWCNT Nanocomposite - Oda, Amjed M.; Khudheyer, Fadhel Y; Obaid, Ehab K. (Iraqi Journal of Science, 2023)
By extracting crystal violate dye (CV) from its aqueous solution, the photocatalytic decolorization performance of ZnO/MWCNT nanocomposite was evaluated. The nanocomposite was prepared by precipitation of ZnO and incorporates on the surface of Multi-Walled Carbon Nanotubes (MWCNT). ZnO nanoparticles were synthesized using the sol gel process with MWCNT acting as a template. They were then analyzed by XRD, SEM, and TEM, which revealed how the shape of the spherical nano ZnO interacts with the point of zero charge (pzc), which allows us to see the physical attributes. In the dipping photoreactor, which included a slurry of dye solution and ZnO/MWCNT nanocomposite, the effectiveness of decolorization was assessed. The photodecolorization was studied for CV dye in aqueous solution at different conditions: The effect of time, weight of catalyst, concentration of dye, temperature, the initial pH of dye solution and addition of S2O82- to show the optimum condition of this process. The main results were the synthesis of incorporated ZnO on MWCNT surface with 10-20 nm with high photodecolorization against CV dye. Full decolorization reached at 90 min and 89.8% decolorization at the half time of reaction. ZnO/MWCNT weight of 0.06 gm per 100 mL was optimum for photodecolorization. The photocatalytic reaction was more efficient in the deceasing of CV concentration and obeys the Langmuir-Hinshelwood kinetic, while the photodecolorization was not less than 95% in pH range 6-10.Also, the photocatalytic reaction was effected in the presence of S2O82-, where the photodecolorization was more efficient.